Constitutive expression of transcription factor SirZ blocks pathogenicity in Leptosphaeria maculans independently of sirodesmin production - Urquhart, Andrew S.; Elliott, Candace E.; Zeng, Wei; Idnurm, Alexander (PLOS ONE, 2021)
Sirodesmin, the major secondary metabolite produced by the plant pathogenic fungus Leptosphaeria maculans in vitro, has been linked to disease on Brassica species since the 1970s, and yet its role has remained ambiguous. Re-examination of gene expression data revealed that all previously described genes and two newly identified genes within the sir gene cluster in the genome are down-regulated during the crucial early establishment stages of blackleg disease on Brassica napus. To test if this is a strategy employed by the fungus to avoid damage to and then detection by the host plant during the L. maculans asymptomatic biotrophic phase, sirodesmin was produced constitutively by overexpressing the sirZ gene encoding the transcription factor that coordinates the regulation of the other genes in the sir cluster. The sirZ over-expression strains had a major reduction in pathogenicity. Mutation of the over-expression construct restored pathogenicity. However, mutation of two genes, sirP and sirG, required for specific steps in the sirodesmin biosynthesis pathway, in the sirZ over-expression background resulted in strains that were unable to synthesize sirodesmin, yet were still non-pathogenic. Elucidating the basis for this pathogenicity defect or finding ways to overexpress sirZ during disease may provide new strategies for the control of blackleg disease.